The Relationship Between Nurses’ Knowledge and Needle Stick Injury Prevention Behavior - Kurniawati, Yunisa Dwi; Suratmi, Suratmi; A., M. Bakri Priyodwi; Qowi, Nurul Hikmatul (Adi Husada Nursing Journal, 2024)
A frequent work accident in the hospitals is needle stick injury. Nurses always contact with blood, patient’s body fluids, punctured needles used by patients and other dangers which can be a medium of disease transmission. The purpose of this study was to determine the relationship between knowledge and needle stick injury prevention behavior. This study used a correlational analytical design with a cross-sectional method, and used cluster sampling techniques to obtain 88 respondents. The data were gathered by using the Lubis questionnaire to measure knowledge and behavior in the prevention of needle stick injury. Then, the data were analyzed by a contingency coefficient test. It was found that 83 nurses (94.3%) had good knowledge and 85 nurses (96.6%) had good behavior. The data about nurses’ knowledge was analyzed and obtained a value of p = 0.000 and a value of contingency coefficient = 0.444, meaning that there was a relationship between knowledge and needle stick injury prevention behavior. Prevention efforts can be carried out by providing guidance, training, direction, and supervision, so that nurses’ awareness increase and they can work safely.